Simple fabrication and comprehensive evaluation of novel nanocomposite for effective methylene blue dye removal from aqueous media - Asma S. Al-Wasidi; Ehab A. Abdelrahman; Reem K. Shah; Fawaz A. Saad (Scientific Reports)
Abstract This study presents the synthesis and evaluation of novel MgO/Ca2PbO4/PbO/C nanocomposites via the Pechini sol–gel method at 600 oC (H600) and 800 oC (H800), for the effective removal of methylene blue (MB) dye from aqueous media. XRD analysis confirmed the formation of well-defined crystalline phases with crystallite sizes of 70.36 nm (H600) and 87.39 nm (H800). EDX results indicated a reduction in carbon content with increasing calcination temperature, while FE-SEM and HR-TEM analyses revealed significant grain and particle growth. Adsorption experiments showed that H600 and H800 exhibited maximum adsorption capacities of 224.72 and 175.13 mg/g, respectively. Kinetic data followed the pseudo-first-order model, and isotherm analysis aligned with the Langmuir model, suggesting monolayer adsorption. Thermodynamic studies indicated that the adsorption process is spontaneous, exothermic, and physical in nature. Overall, the synthesized nanocomposites demonstrate excellent potential as efficient and cost-effective adsorbents for dye-contaminated wastewater treatment.